2013
DOI: 10.1007/s00432-013-1553-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for the development of brain metastases in patients with malignant melanoma: a study by the Anatolian society of medical oncology

Abstract: Our results revealed the importance of primary tumor characteristics associated with the development of BMs. Ulceration, primary tumor thickness, anatomic site, and pathologic ≥N2 disease were found to be significant predictors of BMs development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
2
16
3
Order By: Relevance
“…Our study confirms the correlation of BM development with advanced tumor stage, particularly including Breslow depth >4 mm [5,6,8,11,19] as reported by others. We did not find that ulceration was associated with BM, as seen in two prior studies [10,17], although multiple other studies [5,6,8,9,11] reported a correlation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study confirms the correlation of BM development with advanced tumor stage, particularly including Breslow depth >4 mm [5,6,8,11,19] as reported by others. We did not find that ulceration was associated with BM, as seen in two prior studies [10,17], although multiple other studies [5,6,8,9,11] reported a correlation.…”
Section: Discussionsupporting
confidence: 92%
“…We did not find that ulceration was associated with BM, as seen in two prior studies [10,17], although multiple other studies [5,6,8,9,11] reported a correlation. Curiously, Frankel et al [10] found that thinner primary tumors were associated with BM, although we observed a lower frequency of BM in patients with tumors <1 mm in depth.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations